2010
DOI: 10.1007/s00383-010-2581-x
|View full text |Cite
|
Sign up to set email alerts
|

A review of single site minimally invasive surgery in infants and children

Abstract: Videoscopic surgery has become the standard approach for most thoracic, abdominal, and pelvic procedures in adults and children. These procedures have widely recognized benefits including decreased postoperative pain, improved cosmesis, and decreased convalescence. In a recent attempt to further improve the cosmetic result of these operations, surgeons have begun to employ a single incision through which all the operating instruments are placed. This article seeks to review the current and future application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Recently, in one review article it was reported, that single site approaches to infant operations, such as pyloromyotomy, become quite inapplicable to single site techniques [22]. However, Muensterer et al [2] refuted this definition [20].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, in one review article it was reported, that single site approaches to infant operations, such as pyloromyotomy, become quite inapplicable to single site techniques [22]. However, Muensterer et al [2] refuted this definition [20].…”
Section: Discussionmentioning
confidence: 96%
“…In the field of pediatric surgery, single port surgery using a transumbilical approach has gained popularity during the last few years [7,8,9,10,11,12]. This technique is based on the idea that all laparoscopic trocars are inserted through a single umbilical incision.…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop techniques that are even less invasive compared to the conventional laparoscopic approach and leave less abdominal scars behind, effort has been made to push forward single incision laparoscopic procedures in pediatric surgery (56). SILS is usually carried out through an umbilical incison, using flexible devices through a multi access port, allowing multiple instruments to be inserted at one site.…”
Section: Single Incision Laparoscopic Surgery (Sils)mentioning
confidence: 99%